Trypanosoma cruzi infection in naturally infected dogs from an endemic region of Cundinamarca, Colombia (2018)
The seropositivity and risk factors for Trypanosoma cruzi infection in dogs from a municipality of Cundinamarca, a central state of Colombia were studied. A total of 356 client-owned dogs from urban, peri-urban and rural areas of La Mesa municipality, (Cundinamarca, Colombia) were randomly selected. Blood samples were collected by venipuncture. Anti-T. cruzi antibodies were determined using the enzyme-linked immunosorbent assay (ELISA) method. Reactive ELISA sera were processed by indirect immunofluorescence to confirm the presence of anti-T. cruzi antibodies. Chi-square tests were conducted for statistical analysis. Serologic tests for T. cruzi infection showed a prevalence of 29.49% (105/356), the rural area show a highest T. cruzi infection pattern in comparison with the other zone locations. Two triatomine species were found through the study: Panstrongylus geniculatus (53.4%) and Rhodnius colombiensis (46.6%). The prevalence of positive vectors for parasite was of 52.1% (38/73). Additionally, a very close relation between triatomine bugs and dogs in the rural zone (1:3.1) was observed. These results are the first report of natural infection by T. cruzi in domestic dogs in La Mesa municipality. In conclusion, the presence of anti-T. cruzi antibodies in dogs in this area suggest vector transmission. There is a need for active surveillance programs throughout the La Mesa municipality and vector control strategies should also be implemented. © 2018 Elsevier B.V.